ROLE OF GOVERNMENT OF INDIA IN KASHMIR'S ACCESSION DISPUTE - Chaple, Satish L (ShodhKosh: Journal of Visual and Performing Arts, 2023)
On June 3, 1947, as per the plan announced by the Governor General of India, Lord Mountbatten, Pakistan was created on August 14, 1947 and India on the next day as an independent nation. The princely states that existed at that time were not considered as parts of India or Pakistan and became sovereign according to the Mountbatten plan. Over time, these princely states merged with India or Pakistan. The princely states that were completely bordering India or Pakistan were to join that nation by making a suitable agreement with that nation. Their fate would be decided according to the will of the people of the state. This was the role of the Congress and Lord Mountbatten. For example, Hyderabad, Kolhapur, Bhopal, Junagadh etc. princely states would join India and Bahawalpur, Khairpur, Chitral etc. princely states would join Pakistan. It was thought that the fate of princely states like Kashmir would be decided according to the will of their people. The Congress' position was that if the people of a princely state decided to remain independent, India would accept that too, but that decision should be that of the people, not the state.